ANALISIS KESIAPAN TENAGA KERJA UNTUK PENGEMBANGAN WILAYAH KABUPATEN JAYAWIJAYA - Kosay, Daud; Harmonis Rante, Harmonis; Rusim, Dewi Ana (Magister Perencanaan Wilayah dan Kota Universitas Cenderawasih, 2023)
Jayawijaya as the parent regency in the Central Highlands Region of Papua Province, is the economic center as well as a buffer for the 6 new divisions in the Lapago customary area. This is because the flow of goods and services mobilization that enters the central mountainous region (La Pago) only uses airplanes and the location of the airport is in Wamena City, Jayawijaya Regency. Jayawijaya as the parent regency in the central mountainous region of Papua province, is an economic center as well as a buffer for the 6 expansion districts in the Lapago customary area. This is because the flow of goods and services mobilization that enters the central mountainous region (Lapago) only uses airplanes and the location of the airport is in Wamena, Jayawijaya Regency. regulation. The existence of a policy regulation of the Special Autonomy Law provides opportunities for the Balinese people to get opportunities, both in the fields of education, health and community economic empowerment, and infrastructure. The high unemployment rate in Jayawijaya Regency is due to the low level of Human Resources (HR) in the context of absorbing local workers by the local job market in Jayawijaya district. So Regional Development is essential to increase competitiveness between regions, increase economic growth, reduce inequality between regions, and advance people's lives. Strategic and quality regional development is the hope of Jayawijaya Regency. In this regard, the Government is required to prepare Human Resources (HR) who have competitiveness in the Global Job Market. To prepare human resources to have competitiveness, this can be done, among others, through job training that is carried out in a structured, systematic, and professional manner so that output is produced as expected, namely a competent workforce.